Role of the military in the national security of Guyana - Danns, George K. (Lynne Rienner Boulder, ColoradoUS, 1986)
Argues that Guyanese society represents a significant illustration of growing militarization as a direct response to national security needs. Discusses military expenditure and reviews the history, development and roles of the Army, National Service, Peoples Militia and Guard Service. Examines threats to national security from Venezuela, Suriname and Brazil and Guyana's military assistance to other nations. Points out that internal security problems are reduced to regime preservation. Assesses the implications for the region.